(untitled) (Polish Yearbook of International Law, 2022)
In this article, I present a proposal for an international law-based formula for mediating territorial conﬂicts and apply it to the case of Crimea in Ukraine. Although the tragic Russian attack which commenced on 24 February 2022 has made the mediation even more difcult, once a ceasefre is achieved my formula is capable of providing legally solid compromises to the Ukrainian territorial questions that ft into the contemporary international legal framework concerning territory. Naturally, any realistic solution will require concessions on the part of all stakeholders (primarily Crimea, Ukraine, and Russia). In short, the formula oﬀers for Ukraine the return of its territorial integrity, for Crimea internal self-determination in the form of a meaningful territorial autonomy, and for Russia a few indirect perks and guarantees, mostly related to a possible demilitarization of the Crimean Peninsula. The analysis can also be useful for Donbas, for which the formula oﬀers recognition of some limited autonomous rights.